A novel and sustainable rubber composite prepared from electric arc furnace slag as carbon black replacement - Anna Gobetti; Giovanna Cornacchia; Silvia Agnelli; Mattia Ramini; Giorgio Ramorino (Carbon Resources Conversion, 2024)
Carbon black (CB) is the most widely used reinforcing filler for rubber. Nowadays there are several concerns regarding this traditional petroleum-based filler: on one side its environmental footprint is enormous and its production process is no more sustainable and on the other side its price increases annually. For these reasons, sustainable alternative fillers are being studied. In the present research the main waste of the steel industry, namely the steel slag from electric arc furnace (EAF), is investigated as non-conventional filler for a nitrile butadiene rubber matrix (NBR). The slag has been characterized to ensure its safe reuse as filler according to the heavy metals leaching. The slag filled compounds have been characterized and compared to CB filled compounds, in terms of processability by rheometric parameters, mechanical properties, Payne effect, and physicochemical properties to investigate the filler-matrix interaction. From the obtained results, it was shown that EAF slag-filled NBRs are comparable to CB filled NBRs in terms of crosslink kinetics and, when compared at the same hardness level, are comparable in terms of viscosity, stiffness, and elongation at break, while when compared at the same filler volume fraction are similar in terms of compression set and stress relaxation.